The impact of the initial core temperature on protostellar disc fragmentation. Issue 2 (16th December 2022) - Sigalotti, L Di G; Cruz, F; Hareter, M; Gabbasov, R; Klapp, J; Fierro-Santillán, C R; Ramírez-Velásquez, J M; Zsargó, J
ABSTRACT: Ground-based and satellite observations have revealed dust temperatures as low as ∼5−7 K in the centre of low-mass, pre-stellar cloud cores, where star formation takes place. However, external heating may rise the outer core temperatures up to ∼15−20 K. Such low temperatures at the centre of pre-stellar cores are a key factor to constrain the conditions that lead to the formation of gravitationally bound protostellar systems as was recently captured by highly-resolved Atacama large millimeter/submillimeter array observations. Here, we report consistent smoothed particle hydrodynamics collapse calculations of cold cores that demonstrate the formation of close protobinary systems via small-scale fragmentation of a gravitationally unstable protostellar disc. The results indicate that mean binary separations, of tens of astronomical units, are a consequence of disc fragmentation in cold pre-stellar cores. Cloud cores initially with temperatures ≤6 K and a low amplitude ( a = 0.1), m = 2 density perturbation formed close protobinaries that were followed deep into the non-isothermal collapse for several orbital periods and appeared to survive as independent stellar entities. At temperatures ≥7 K disc fragmentation is no longer observed and the calculations terminate with the formation of a wide protobinary, which may occasionally be accompanied by small substellar objects emerging by fragmentation of the circumbinary disc. When the perturbation amplitude is raised to a = 0.25, disc fragmentation occurs again only in cores with initial temperatures ≤6 K. Therefore, increasing the perturbation amplitude does not necessarily imply that there will be disc fragmentation at higher core temperatures.